TEACHER'S SPEECH ACTS AND CLASSROOM INTERACTION STRATEGIES IN AN EFL SETTING: A PRAGMATIC ANALYSIS OF ORAL DISCOURSE - Yoga Marcell Karosekali; M. Rafif Zaki Ramadhan; Jose Christian Sianipar; Johannes Jefria Gultom (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study investigates the pragmatic dimensions of teacher talk in an Indonesian EFL classroom at MAS Ponpes Darul Qur'an, a pesantren-based Islamic senior high school. Focusing on a complete lesson on descriptive text, the study examines two interrelated dimensions: (1) the types of speech acts performed by the teacher, analyzed through Austin's (1962) tripartite framework and Searle's (1969, 1979) illocutionary taxonomy; and (2) the teacher's questioning strategies, analyzed through Long and Sato's (1983) display–referential–echoic questioning framework. Data were collected via non-participant classroom observation and video recording, and analyzed using Miles, Huberman, and Saldaña's (2014) interactive qualitative model. Findings reveal that expositives and exercitives dominate the illocutionary repertoire, behabitives are strategically placed at affectively critical moments, and referential questions appear at a notably higher proportion than comparable studies report—attributable to the teacher's use of culturally resonant topics. Critically, the most acquisitionally significant moments arose from the convergence of referential questioning, echoic follow-up, and affective speech acts, constituting a cross-framework synergy uniquely situated within the pesantren classroom context